Diagnostic and prognostic significance of mRNA expressions of apolipoprotein A and C family genes in hepatitis B virus‐related hepatocellular carcinoma. Issue 10 (18th June 2019) - Wang, Xiangkun; Gong, Yizhen; Deng, Teng; Zhang, Linbo; Liao, Xiwen; Han, Chuangye; Yang, Chengkun; Huang, Jianlu; Wang, Qiaoqi; Song, Xiaowei; Zhang, Tengfang; Yu, Tingdong; et al.
Abstract: Background: Hepatocellular carcinoma (HCC) is among the most common and lethal malignancies worldwide. Apolipoproteins (APOs) have been reported increasingly for their relationships with tumors. We aim at exploring the potential relationships of apolipoprotein A (APOA) and apolipoprotein C (APOC) family members with HCC. Methods: A data set, containing 212 hepatitis B virus‐related HCC patients, was used for analysis. The diagnostic and prognostic ability of APOA and APOC family genes was figured out. Risk score models and nomograms were developed for the HCC prognosis prediction. Moreover, molecular mechanism exploration were identified biological processes and metabolic pathways of these genes involved in. Validation analysis was carried out using online website. Results: APOA1, APOC1, APOC3, and APOC4 showed robust diagnosis significance (all P < 0.05). APOA4, APOC3, and APOC4 were associated with the overall survival (OS) while APOA4 and APOC4 were linked to recurrence‐free survival (RFS, all P ≤ 0.05). Risk score models and nomograms had the advantage of predicting OS and RFS for HCC. Molecular mechanism exploration indicated that these genes were involved in the steroid metabolic process, the PPAR signaling pathway, and fatty acid metabolism. Besides that, validation analysis revealed that APOC1 and APOC4 had an association with OS; and APOC3 was associated with OS and RFS (all P ≤ 0.05). Conclusions: APOA1, APOC1, APOC3, and APOC4 are likely to be potential diagnostic biomarkers and APOC3 and APOC4 are likely to be potential prognostic biomarkers for hepatitis B virus‐related HCC. They may be involved in the steroid metabolic process, PPAR signaling pathway, and fatty acid metabolism. Abstract : Our present study found that APOA1, APOC1, APOC3, and APOC4 are likely to be potential diagnostic biomarkers and APOC3 and APOC4 are likely to be potential prognostic biomarkers for hepatitis B virus‐related HCC. They may be involved in the steroid metabolic process, PPAR signaling pathway, and fatty acid metabolism.